Relationship between Carbohydrate, Protein, and Fat Consumption with Obesity Incidence in 2014 UKI Faculty of Medicine Students - Ago Harlim; Stella Irene Bontong; Mohammad Zen Rahfiludin (Amerta Nutrition, 2022)
Background: Obesity is an excessive fat accumulation in the body. Excessive consumption of carbohydrates, protein, and fat can increase the risk of obesity. It occurs when there is an imbalance between the energy number that goes through food and the energy that comes out through physical activity. Objectives: This study aimed to know the relationship between carbohydrate, protein, and fat consumption and obesity among the 2014 UKI Faculty of Medicine Students. Methods: This study was analytical observational research with a case-control design. The samples were 68 students from batch 2014. The data are analyzed by SPSS using Chi-square and logistic regression. Results: A total of 27.9% of students were obese, of which 33.3% were male and 25.5% were female. Based on the results of bivariate analysis, there was a significant relationship between obesity and protein consumption (p=0.048) and fat consumption (p=0.035), while there was no correlation between obesity incidence and carbohydrate consumption (p= 0.373). Conclusions: The incidence of obesity in UKI Medicine Students batch 2014 was caused by the high consumption of fat and protein. It was not caused by the consumption of carbohydrates.